Normal mast cell numbers in the tissues of AhR‐deficient mice. Issue 1 (23rd November 2015) - Pilz, Caroline; Feyerabend, Thorsten; Sonner, Jana; Redaelli, Chiara; Peter, Katharina; Kunze, Anja; Haas, Katharina; Esser, Charlotte; Schäkel, Knut; Wick, Wolfgang; Rodewald, Hans‐Reimer; Lanz, Tobias V.; et al.
Abstract: The transcription factor aryl hydrocarbon receptor (AhR) acts as an immunomodulatory molecule in several immune cell lineages. Recently, it has been implicated in development and maintenance of immune cells in barrier tissues such as skin and mucosa. To investigate its role on mast cell development and maintenance in skin, peritoneal exudate cells (PECs) and lymph nodes, we studied in depth their phenotype in AhR‐deficient mice. Our findings do not provide any evidence for a suspected role of the AhR in mast cell homeostasis.